Evaluasi Pengembangan Pembelajaran Biologi Berbasis Media e-Learning pada Mahasiswa Tadris Biologi 3 Semester VI Universitas Islam Negeri Sumatera Utara - Oktariani, Puput; Pasaribu, Kana Furkonah; Khairunnisa, Azra; Amina, Siti; Sari, Sri Melina; Adiesty, Zahwa (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Learning is inseparable from evaluation. With the development of time and technological advancement, various learning media have emerged. e-Learning has become a solution to the current technological advancements. Learning methods using technology are greatly needed in various learning places, be it schools or universities. This research uses the research and development method. The purpose of this research is to find out the development of e-learning-based learning. The data results that the researchers will obtain are the responses of Students of Biology Education 3, 6th Semester, UINSU. Hopefully, this article can be an alternative choice or reference in learning.